2021
DOI: 10.1111/ajt.16267
|View full text |Cite
|
Sign up to set email alerts
|

Lung donation after medical assistance in dying at home

Abstract: Organ donation after medical assistance in dying (MAID) has only been possible for patients having the MAID procedure performed at a hospital facility due to prohibitive warm ischemic times. Herein, we describe a protocol for lung donation following MAID at home and demonstrate excellent postoperative outcomes. Lung donation following MAID at home is possible and should be considered by transplant programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 9 publications
(20 reference statements)
0
48
0
3
Order By: Relevance
“…Based on our experience with controlled DCD and uncontrolled DCD transplantation, using the same principles, we were able to devise a protocol for proper lung preservation after death declaration so that the donor could be transported to nearest hospital for organ retrieval to take place. 8 When we initiated this practice, we adopted a conservative practice by evaluating the function of these MAID donor lungs in all cases using EVLP. As we acquired further experience and confidence in our assessment process, we moved to a protocol of using EVLP when there are concerns in the on-site donor assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our experience with controlled DCD and uncontrolled DCD transplantation, using the same principles, we were able to devise a protocol for proper lung preservation after death declaration so that the donor could be transported to nearest hospital for organ retrieval to take place. 8 When we initiated this practice, we adopted a conservative practice by evaluating the function of these MAID donor lungs in all cases using EVLP. As we acquired further experience and confidence in our assessment process, we moved to a protocol of using EVLP when there are concerns in the on-site donor assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The logistic details of MAID provision at home were described in a recent case report. 8 Briefly, MAID and the offer of lung donation were requested voluntarily. MAID drugs were given by clinicians at home.…”
Section: Maid Indication Consent and Proceduresmentioning
confidence: 99%
“…These donors have not underwent brain death nor associated cytokine storm 9 , which have a negative impact on isolation yield and in vivo function 10 . DCD V lung recipients showed good early graft function 33 , even when the procedure is initiated outside the hospital 34 . A recent study reported equal short- and long-term outcome as for DCD III and DBD 35 .…”
Section: Discussionmentioning
confidence: 99%
“…We have described the successful technique for MAID donation with death at home followed by LTx. 49 This type case requires additional logistical organization to maximize preservation of the lung, including transportation of the intubated donor in a prone position with passive lung inflation and ready operating room (OR) resources. However, at first discussion and to ultimately help as many recipients as possible, it is important to continue to offer admission to hospital which allows for multiorgan donation from a MAID donor.…”
Section: Controlled and Uncontrolled Donation After Cardiac Deathmentioning
confidence: 99%